2020
DOI: 10.1109/access.2020.3019336
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of the Application of Convolutional Neural Network in Computer Vision

Abstract: This paper analyzes the research progress in field of Convolutional Neural Networks(CNNs) using the bibliometric method. Literature samples of CNNs are analyzed by a basic statistic and co-citation network. Experimental results show that CNNs are being utilized in many computer vision applications, such as fault and image recognition diagnosis, seismic detection, positioning, and automatic detection of cracks and signals, image classification and image segmentation. In addition, there is systematic research on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Out of 10 research institutes, four of them are in China while two in Canada and one each are in the United States, India, the Netherlands, and Sweden. This finding implies that convolutional neural network and deep learning-related research has improved in China over these years [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of 10 research institutes, four of them are in China while two in Canada and one each are in the United States, India, the Netherlands, and Sweden. This finding implies that convolutional neural network and deep learning-related research has improved in China over these years [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are also several bibliometric studies concerning other topics that mention object detection in their findings. Chen and Deng [4] conducted a bibliometric analysis regarding the application of Convolutional Neural Networks (CNNs) in CV. Published in 2020, their study concluded that object detection and location are the hottest areas in relation to CNN research.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Are widely applied in computer vision (Chen and Qi 2019). A typical CNN consists of convolutional layers, pooling layers, and fully connected layers.…”
Section: Convolutional Neural Network (Cnns)mentioning
confidence: 99%